Mechanism model for shale gas transport considering diffusion, adsorption/desorption and Darcy flow - Wei, Ming-qiang; Duan, Yong-gang; Fang, Quan-tang; Wang, Rong; Yu, Bo-ming; Yu, Chun-sheng (Journal of Central South University, 2013)
To improve the understanding of the transport mechanism in shale gas reservoirs and build a theoretical basic for further researches on productivity evaluation and efficient exploitation, various gas transport mechanisms within a shale gas reservoir exploited by a horizontal well were thoroughly investigated, which took diffusion, adsorption/desorption and Darcy flow into account. The characteristics of diffusion in nano-scale pores in matrix and desorption on the matrix surface were both considered in the improved differential equations for seepage flow. By integrating the Langmuir isotherm desorption items into the new total dimensionless compression coefficient in matrix, the transport function and seepage flow could be formalized, simplified and consistent with the conventional form of diffusion equation. Furthermore, by utilizing the Laplace change and Sethfest inversion changes, the calculated results were obtained and further discussions indicated that transfer mechanisms were influenced by diffusion, adsorption/desorption. The research shows that when the matrix permeability is closed to magnitude of 10 −9 D, the matrix flow only occurs near the surfacial matrix; as to the actual production, the central matrix blocks are barely involved in the production; the closer to the surface of matrix, the lower the pressure is and the more obvious the diffusion effect is; the behavior of adsorption/desorption can increase the matrix flow rate significantly and slow down the pressure of horizontal well obviously.